2017
DOI: 10.1039/c6an02565j
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bifurcations with signal enhancement in nonlinear mid-infrared thermal lens spectroscopy

Abstract: We report a novel nonlinear mid-infrared vibrational spectroscopy regime where multiple bifurcations and signal enhancement are observed in the photothermal spectrum of a 6 μm-thick layer of 4-octyl-4'-cyanobiphenyl (8CB) liquid crystal. For increasing pump power values, the nonlinear evolution of the photothermal spectrum is studied in 8CB samples initially in the crystalline and smectic-A phase and their non-equilibrium transitions are characterized with pump-probe thermal lens spectroscopy. The nonlinear ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This study generalizes ideas from optics to chemical imaging microscopes and can be extended to other emerging techniques as well as modalities with different mechanisms of chemical contrast. One exciting new area is the combination of infrared and optical frequencies to record data by using the photothermal effect, for example. The probing wavelength in these cases is much shorter (typically, visible), which facilitates submicrometer optical resolution but does not yet provide the SNR of all-IR laser scanning microscopy .…”
Section: Resultsmentioning
confidence: 99%
“…This study generalizes ideas from optics to chemical imaging microscopes and can be extended to other emerging techniques as well as modalities with different mechanisms of chemical contrast. One exciting new area is the combination of infrared and optical frequencies to record data by using the photothermal effect, for example. The probing wavelength in these cases is much shorter (typically, visible), which facilitates submicrometer optical resolution but does not yet provide the SNR of all-IR laser scanning microscopy .…”
Section: Resultsmentioning
confidence: 99%
“…We show numerically that the Lorentzian map is characterized by single bifurcation point, which can be used to simulate certain non linear phenomena reported experimentally in°uid mechanics 12 where the velocity pro¯le of the°uid in rectangular geometry is characterized by two stable states in laminar°ow with respect to the dimensions of the channel. Additionally, similar pattern of double period bifurcation found in Lorentzian map was also observed in optical spectroscopy 13 where liquid crystal characterization using laser showed that the measured spectra with respect to the input power of the laser contains second-order bifurcation.…”
Section: Introductionmentioning
confidence: 52%
“…The experimental results of recent study, 13 reported the bifurcation of the measured output power of the response of (8CB) liquid crystal, using¯ber laser probe. By changing the temperature, photo thermal spectra gave di®erent phases such as crystalline and disordered phases.…”
Section: Lorentzian Bifurcationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a conference proceeding, Furstenberg et al (46) reported chemical imaging of small crystals and polymer coating on microelectromechanical systems using a reflection photothermal microscope. Erramilli and Sander's group reported photothermal IR spectra of liquid crystal and showed the nonlinear Zharov peak splitting with QCL as pump beam (47)(48)(49)(50). Mërtiri et al (51) demonstrated a mid-IR pump, near-IR probe photothermal imaging using a reflective objective lens and showed a photothermal image of a dried bird brain tissue slice.…”
Section: Introductionmentioning
confidence: 99%